2005
DOI: 10.1051/lait:2005042
|View full text |Cite
|
Sign up to set email alerts
|

Respective effects of milk composition and the cheese-making process on cheese compositional variability in components of nutritional interest

Abstract: -To assess the relationship between conditions of milk production and cheese contents of components of nutritional interest, it is necessary to know to what extent the compositional variability of cheese depends on that of milk. The respective effects of milk composition and the cheese-making process on cheese compositional variability in components of nutritional interest were therefore studied under real conditions of cheese production considering four different cheese-making technologies. The nutritional ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
110
2
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 126 publications
(137 citation statements)
references
References 71 publications
(89 reference statements)
20
110
2
3
Order By: Relevance
“…In a previous study [48], we showed that the cheese composition in FA, carotenoids and α-tocopherol, as well as to a lesser extent in retinol, mainly depends on the milk composition and consequently on the conditions of milk production. Similarly, the total antioxidant capacity (TAC) in cheese could also be influenced by the conditions of milk production.…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…In a previous study [48], we showed that the cheese composition in FA, carotenoids and α-tocopherol, as well as to a lesser extent in retinol, mainly depends on the milk composition and consequently on the conditions of milk production. Similarly, the total antioxidant capacity (TAC) in cheese could also be influenced by the conditions of milk production.…”
Section: Introductionmentioning
confidence: 88%
“…Three French farmhouse cow's raw milk cheese varieties were studied: Abondance cheese (pressed semi-cooked cheese) and Tomme de Savoie cheese (pressed uncooked cheese) in the Northern Alps area, and Cantal-type cheese (pressed uncooked cheese) in the Massif Central area. The main characteristics of these cheeses have been previously described [48]. In total, 54 farms were sampled by the producer trade unions of these cheeses so as to have a farm sample representing the existing broadness of the conditions of milk production.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations